Structures and properties of side-chain liquid crystalline polynorbornenes containing an amide group: hydrogen bonding interactions and spacer length effects - Shi, Dong; Chang, Wen-Ying; Ren, Xiang-Kui; Yang, Shuang; Chen, Er-Qiang (Polymer chemistry, 2020)
To investigate the structure-property relationship of side-chain liquid crystalline (LC) polymers with specific interactions, we synthesized a series of polynorbornene derivatives bearing benzanilide side-chains (denoted as P8- n , where n represents the number of methylene units in the spacer, and the number 8 indicates the side-chain tail of the octyl group). For comparison, a reference polynorbornene derivative (denoted as P8-6-E ) was also synthesized by replacing the amide group in the rod-like mesogen with an ester group. It is found that with the polynorbornene main-chain the samples can exhibit rich LC behaviors, different from other benzanilide-containing polymers. P8-2 and P8-4 form a bilayer smectic C (SmC 2 ) phase. On the other hand, with longer spacers, the molecules of P8-8 and P8-10 can pack into a highly ordered structure (denoted as X 1 ). The X 1 phase has an orthorhombic lattice with the side- and main-chains along the c - and b -axes, wherein the side-chains show interdigitated packing with some features of a crystal E (CrE) structure. For P8-6 , some bilayer CrE domains may coexist with X 1 , resulting in a mixed phase of X 1 /E 2 . It is unveiled that the amide group at the center of benzanilide always tends to form hydrogen bonds, leading to the unique molecular packing of P8- n s which is dependent on the size matching between the spacer and tail. Moreover, weakening the hydrogen bonds in P8- n s ( n ≥ 8) could induce a phase transition from X 1 to X 1 /E 2 . Compared with the rather soft and ductile P8-6-E with a smectic B phase, P8- n s show much higher Young's moduli because of the presence of lateral hydrogen bonds. While those with the X 1 phase are brittle, the P8- n s with a SmC 2 structure exhibit better overall mechanical properties, rendering a breaking strain of ∼450%. Side-chain liquid crystalline polynorbornenes based on benzanilide mesogens exhibit rich self-organization behaviours and enhanced mechanical properties owing to the lateral hydrogen bond interaction that can be tuned by the spacer length.